Efficient Monofluoroalkylation of Thiophenols or Phenols with α-Bromo-α-Fluoroketones under Mild Conditions - Li, Zhi; Fang, Mougui; Wu, Jingjing; Liu, Yunli; Liu, Yecheng; Wu, Fanhong (Synthesis, 2021)
An efficient nucleophilic substitution reaction between α-bromo-α-fluoroketones and thiophenols or phenols is reported for the synthesis of α-fluoro-β-ketosulfides or α-fluoro-β-ketone ethers in yields ranging from 78–93%. This method exhibits good functional group tolerance and a broad scope of nucleophilic substrates, including natural phenolic compounds.
Keywords: monofluoroalkyltion; nucleophilic substitution; α-bromo-α-fluoroketones; α-fluoro-β-ketosulfides; α-fluoro-β-ketone ethers